Les pratiques commerciales dans une région frontalière. Les exemples d’Arlon, de Luxembourg-ville et de Metz - Smits, Florence (Belgeo, 2006)
Abstract: „Parts of Belgium, France, Germany and Luxembourg which comprise the Great Region have witnessed an increase in the mobility of workers and in the degree of political collaboration. Nevertheless, this evolution does not seem to have had an impact on the consumption habits of workers who tend to remain quite different in Arlon, Luxembourg and Metz. In contrast, people with less mobility but more time available, such as the retired and young, seem to exhibit the same pattern of consumption.“
Keywords: Arlon; Einkaufen; Grenzarbeitnehmer; Handel; Luxemburg (Stadt); Metz; Mobilität; Verbrauch

Garder la frontière. Le comte de Belle-Isle dans les Trois-Évêchés de 1727 à l´ouverture de la guerre de Succession de Pologne - Lasconjarias, Guillaume (Hypothèses, 2005)
Keywords: Grenzgebiet; Metz; Militär